Pengaruh Pendidikan Kesehatan Terhadap Perilaku Pemangku Adat Dalam Penemuan Kasus TB - Petrus Belarminus; Grasiana Florida Boa; Maria Ch Endang. S (Poltekkes Kemenkes Kupang, 2020)
Introduction: Find the TB cases is the first step to TB client medication stage. Find and treat the TB infectious client steadily will reduction the number of the infectious and deadly cases. Besides, it could be the best preventive action to stop the TB amount. The best strategy to catch the TB suspect is by make a good collaboration with the district community by the involved of customary stakeholder (Rato). The purpose of this research is to know the effect of health education to the Rato behavior (knowledge, attitudes and actions) also other factor that influence the Rato in deciding the best treatment need for the TB suspect at Wanukaka regions. Method: this research is a quantitative research using the Quasi Experimental Pre-Posttest with Control Group research design. The sample are taken with Purpose Sampling. There are 28 subjects of Wanukaka region locality customary stakeholders. Fourteen of them are for intervention group and 14 others for the controlling group. The intervention given is three times of health education. Results: the analysis show that the health education effects the increasing of knowledge and attitude toward p value < 0,005, also show that there is difference of knowledge and behavior in deciding the best attitude toward the TB suspect to the intervention group and the control group p value < 0,005. With an increase in the value of knowledge in the intervention group by 11.5 points and a change in the value of the attitude of the intervention group by 10.71 points, as well as showing differences in knowledge and attitudes in TB case finding in the intervention group and the control group. Conclusion: This study shows that health education influences the behavior of RATO in TB case finding in Wanukaka. Pendahuluan: Penemuan kasus merupakan langkah pertama dalam kegiatan tatalaksana klien TB. Penemuan dan penyembuhan klien TB secara bermakna akan menurunkan angka kesakitan dan kematian serta merupakan kegiatan pencegahan penularan TB yang paling efektif di masyarakat. Strategi kunci untuk dapat menemukan kasus TB adalah dengan melibatkan peran serta masyarakat termasuk tokoh adat (Rato). Tujuan penelitian ini adalah diketahuinya pengaruh pendidikan kesehatan terhadap perilaku pemangku adat (Rato) dalam penemuan Kasus TB. Metode: penelitian Quasi Eksperimental Pre-Post test with Control Group desain. Teknik pengambilan sampel dengan total sampling. Jumlah responden masing-masing 14 orang untuk kelompok intervensi dan 14 orang untuk kelompok kontrol. Intervensi yang diberikan adalah pendidikan kesehatan yang dilakukan sebanyak 3 kali. Hasil: analisis menunjukan bahwa pendidikan kesehatan berpengaruh terhadap peningkatan pengetahuan sikap dan tindakan dengan p value 0,005 < 0,05. Dengan peningkatan nilai pengetahuan pada kelompok intervensi sebesar 11,5 poin dan perubahan nilai sikap kelompok intervensi sebesar 10,71 poin, serta menunjukan ada perbedaan pengetahuan dan sikap dalam penemuan kasus TB pada kelompok intervensi dan kelompok kontrol. Kesimpulan: Penelitian ini menunjukkan bahwa pendidikan kesehatan mempengaruhi perilaku RATO dalam penemuan kasus TBC di Wanukaka.